The technology of patriotic education of Russian police officers: Countering anti-patriotism as a destructive pedagogical factor - Sergey N. Kipreev; Maria N. Girnik; Victor M. Lyapin; Sergey A. Vakhrushev (Russian Journal of Education and Psychology)
Background. This article examines the phenomenon of "anti-patriotic myths". The author points out the possibility of developing a destructive worldview among people with anti-patriotic views, which can lead to the formation of a sectarian worldview, extremist and terrorist views.